Analisis Penggunaan Metode All or Nothing Assignment dalam Mengestimasi Rute Transportasi Menuju Universitas Palangka Raya - Putri Elicabeth Manalu; Sutan Parasian Silitonga; Desriantomy Desriantomy (Fakultas Teknik, 2023)
The number of students who increase every year has an impact on increasing traffic usage, and traffic conditions have a negative impact on the less than optimal operation of existing facilities, such as on-street parking lots located in several different places. In this study, the problem is how the transportation route to Palangka Raya University is currently which aims to determine the load of road sections based on the shortest route taken by a vehicle from the starting point to Palangka Raya University. Data collection is done by distributing online questionnaires, namely via google form, the data obtained is processed with Microsoft excel with descriptive analysis method. Based on the results obtained, the route choice on Jalan Rajawali is dominated by the route Jalan Badak III-Jalan Lele-Jalan Tingang-Jalan Bukit Kaminting 89%, on Seth Adji road, namely the route Jalan Nyai Undang - Jalan RTA Milono - Jalan Raden Saleh - Jalan G. Obos - Jalan Sultan Hasannudin. Obos - Jalan Sultan Hasannudin - Jalan Yos Sudarso as much as 69%, on Jalan Ahmad Yani, namely the route Jalan Sulawesi - Jalan A.Yani - Jalan Di Panjaitan - Roundabout Besar Palangka Raya - Jalan Yos Sudarso 81%, and on Jalan RTA Milono, namely the route Palangka Raya Bird Roundabout - Jalan Temanggung Tilung - Jalan G.Obos - Jalan Galaxy Raya - Jalan Yos Sudarso 81%. From the results it can be concluded that the route choice factor based on the shortest travel distance affects students in choosing transportation routes.